1994
DOI: 10.1007/bf00431548
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of crystal matrix protein as a potent inhibitor of calcium oxalate crystal aggregation: evidence of activation peptide of human prothrombin

Abstract: In order to clarify the characteristics of crystal matrix protein (CMP), which exhibits a remarkable affinity for calcium oxalate crystals and may be important in stone pathogenesis, we have isolated CMP from macromolecular matrix substances of newly-formed calcium oxalate crystals. Purification of CMP consisted of calcium oxalate crystal formation, dissolution of crystals, electrodialysis, anion exchange chromatography and high-performance liquid chromatography. CMP showed the protein band of 31 kDa in sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
5
32
0
Order By: Relevance
“…The inhibitory effects of osteopontin and prothrombin fragment 1 on the crystallization and aggregation of CaOx crystals have been reported. 25,26 Protein Z, protein S, and prothrombin, which are vitamin K-dependent calcium-binding proteins, are thought to act as regulators in the coagulation process. 27,28 These proteins have a Gla-containing domain that is able to chelate calcium ions.…”
Section: Proteins Identified In Stones Using Lc-ms/msmentioning
confidence: 99%
“…The inhibitory effects of osteopontin and prothrombin fragment 1 on the crystallization and aggregation of CaOx crystals have been reported. 25,26 Protein Z, protein S, and prothrombin, which are vitamin K-dependent calcium-binding proteins, are thought to act as regulators in the coagulation process. 27,28 These proteins have a Gla-containing domain that is able to chelate calcium ions.…”
Section: Proteins Identified In Stones Using Lc-ms/msmentioning
confidence: 99%
“…Blots were stained with Coomassie blue (0.1%), destained with 50% methanol and 10% acetic acid, and the predominant band at 39 kDa was excised. Amino acid compositional analysis, performed at the University of Chicago Amino Acid and Protein Core Lab, is shown in Table 1, in which CAI is compared with three other urinary crystallization inhibitors, uropontin (UP) (31), human urinary prothrombin fragment 1 (UPTF1) (33), and bikunin (34). Whereas the estimated total net charges on the protein core of UP (Ϫ25.5), UPTF1 (Ϫ14.3), and bikunin (Ϫ7.4) are each negative, CAI (Ϫ2.1) was nearly neutral.…”
Section: Cultured Renal Cells Constitutively Release Cai Binding Of mentioning
confidence: 99%
“…First of all, it is worthwhile to mention that crystals were washed only with distilled water rather than sodium hydroxide solution as described by some investigators [10][11][12][13]. Recently, we have reported that this procedure of washing contributes to the loss of most THP and albumin [14].…”
Section: Analysis Of Crystal Matrix Proteinsmentioning
confidence: 99%
“…In this regard, it was proposed to analyze proteins extracted from calcium oxalate (CaOx) crystals induced in vitro in normal urine [10][11][12]. The results showed a highly selective incorporation of prothrombin fragment 1 [12,13]. Subsequently, it was concluded that this protein plays an important role in urinary stone formation.…”
Section: Introductionmentioning
confidence: 99%